Reset control of integrating plus dead time processes. (February 2016) - Davó, M.A.; Baños, A.
Abstract : Highlights: A control scheme based on a reset proportional integral compensator is investigated. The tuning rule has a free parameter to balance between robustness and performance. A new reset strategy improves the load disturbance rejection. The proposed tuning rule is compared with the best known traditional tuning approaches. The proposed compensator is tested in a real experiment of liquid level control. Abstract: This work develops a tuning method for a reset compensator and an integrating plus dead time system. The reset compensator consists of a proportional integral compensator plus a Clegg integrator (PI+CI), and is equipped with a variable band resetting law, which allows to reduce the harmful effect of time-delay, and a switching reset ratio that obtains a superior performance in comparison with a well-tuned PI compensator. This work exposes a simple tuning rule for setting all the parameters of the PI+CI compensator with the aim of improving both setpoint tracking and load disturbance rejection. A case study is analyzed by simulation, discussing both performance and robustness of several PI+CI and PI compensators. Finally, an experiment of liquid level control shows the advantages of the proposed reset compensator.